Loss of Angiotensin II Type 2 Receptor Improves Blood Pressure in Elastin Insufficiency - Lin, Michelle; Roth, Robyn A.; Kozel, Beth A.; Mecham, Robert P.; Halabi, Carmen M. (Frontiers in Cardiovascular Medicine, 2021)
There is ample evidence supporting a role for angiotensin II type 2 receptor (AT2R) in counterbalancing the effects of angiotensin II (ang II) through the angiotensin II type 1 receptor by promoting vasodilation and having anti-inflammatory effects. Elastin insufficiency in both humans and mice results in large artery stiffness and systolic hypertension. Unexpectedly, mesenteric arteries from elastin insufficient (Eln+/−) mice were shown to have significant vasoconstriction to AT2R agonism in vitro suggesting that AT2R may have vasoconstrictor effects in elastin insufficiency. Given the potential promise for the use of AT2R agonists clinically, the goal of this study was to determine whether AT2R has vasoconstrictive effects in elastin insufficiency in vivo. To avoid off-target effects of agonists and antagonists, mice lacking AT2R (Agtr2−/Y) were bred to Eln+/− mice and cardiovascular parameters were assessed in wild-type (WT), Agtr2−/Y, Eln+/−, and Agtr2−/Y;Eln+/− littermates. As previously published, Agtr2−/Y mice were normotensive at baseline and had no large artery stiffness, while Eln+/− mice exhibited systolic hypertension and large artery stiffness. Loss of AT2R in Eln+/− mice did not affect large artery stiffness or arterial structure but resulted in significant reduction of both systolic and diastolic blood pressure. These data support a potential vasocontractile role for AT2R in elastin insufficiency. Careful consideration and investigation are necessary to determine the patient population that might benefit from the use of AT2R agonists.